Siponimod pharmacokinetics, safety, and tolerability in combination with the potent CYP3A4 inhibitor itraconazole in healthy subjects with different CYP2C9 genotypes - Gardin, Anne; Shakeri-Nejad, Kasra; Feller, Andrea; Huth, Felix; Neelakantham, Srikanth; Dumitras, Swati (European journal of clinical pharmacology, 2019)
Purpose To evaluate the PK and safety of siponimod, a substrate of CYP2C9/3A4, in the presence or absence of a CYP3A4 inhibitor, itraconazole. Methods This was an open-label study in healthy subjects (aged 18–50 years; genotype: CYP2C9 *1*2 [cohort 1; n = 17] or *1*3 [cohort 2; n = 13]). Subjects received siponimod 0.25-mg single dose in treatment period 1 (days 1–14), itraconazole 100 mg twice daily in treatment period 2 (days 15–18), and siponimod 0.25-mg single dose (day 19) with itraconazole until day 31 (cohort 1) or day 35 (cohort 2) in treatment period 3. PK of siponimod alone and with itraconazole and safety were assessed. Results Overall, 29/30 subjects completed the study. In treatment period 1, geometric mean AUC inf , T 1/2 , and median T max were higher while systemic clearance was lower in cohort 2 than cohort 1. In treatment period 3, siponimod AUC decreased by 10% (geo-mean ratio [90% confidence intervals]: 0.90 [0.84; 0.96]) and 24% (0.76 [0.69; 0.82]) in cohorts 1 and 2, respectively. Siponimod C max was similar between treatment periods 1 and 3. In both cohorts, the C max and AUC of the metabolites (M17, M3, and M5) decreased in the presence of itraconazole. All adverse events were mild. Conclusions The minor albeit significant reduction in plasma exposure of siponimod and its metabolites by itraconazole was unexpected. While the reason is unclear, the results suggest that coadministration of the two drugs would not cause a considerable increase of siponimod exposure independent of CYP2C9 genotype.